Pendampingan Digital Marketing Sebagai Strategi Pemasaran UMKM Budidaya Lele Al-Qolam Fish Farm - Gideon Setyo Budiwidjaksono; Andini Novianti; Alaufi Khairunisya; Muara Ati Asri Ariasta; Hana Nazara Putri; Mochammad Rayyan Thalib (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
UMKM Al-Qolam Fish Farm is one of the businesses located in Tanjungsari Village, Sukorejo District, Blitar City. This UMKM is engaged in catfish cultivation. The lack of knowledge and information about digital marketing has resulted in the marketing of UMKM Al-Qolam Fish Farm products being limited to conventional media. Therefore, there is a need for outreach and assistance regarding the importance of digital marketing and the benefits of this type of marketing to Al-Qolam Fish Farm UMKM. The methods used in this service are surveys, questionnaires, outreach, FGDs, and assistance to UMKM. The results of this study, Al-Qolam Fish,Farm can understand the benefits and importance of digital marketing. These UMKM also know the platforms that can be used for digital marketing. In addition, these UMKM also understand how to create and run websites through the Google Site and TikTok social media accounts. It is hoped that the socialization and mentoring activities carried out for UMKM can increase the sustainability and competitiveness of UMKM Al-Qolam Fish Farm in the current digital era.